Effect of Age at Pediatric Stroke on Long-term Cognitive Outcome. (15th February 2022) - Abgottspon, Stephanie; Thaqi, Qendresa; Steiner, Leonie; Slavova, Nedelina; Grunt, Sebastian; Steinlin, Maja; Everts, Regula
Abstract : Background and Objectives: To investigate the effect of age at pediatric arterial ischemic stroke on long-term cognitive outcome in order to identify patients particularly at risk for the development of long-term cognitive sequelae. Methods: This cross-sectional study included patients in the chronic phase of stroke (>2 years after stroke) previously diagnosed with neonatal or childhood arterial ischemic stroke and a control group. Participants with active epilepsy, severe learning difficulties, or behavioral problems hindering the cognitive assessment were excluded. Several cognitive domains, including intelligence, executive functions (working memory, inhibition, and cognitive flexibility), processing speed, memory, letter fluency, and visual-motor skills were assessed with neuropsychological tests. Cognitive long-term outcome was compared across patients after neonatal stroke (stroke between 0 and 28 days of life), early childhood stroke (stroke between 29 days and <6 years), and late childhood stroke (stroke between ≥6 and <16 years). Results: Fifty-two patients after neonatal or childhood arterial ischemic stroke (median age 15.3 years, interquartile range [IQR] 10.6–18.7) and 49 healthy controls (median age 13.6 years, IQR 9.8–17.2) met the inclusion criteria. Cognitive outcome was significantly worse in the pediatric stroke group compared to the control group. A nonlinear effect of age at stroke (irrespective of lesion size and lesion location) was found for cognitive flexibility, processing speed, and verbal learning with early childhood stroke (29 days to <6 years), showing significantly worse cognitive outcome compared to neonatal or late childhood stroke ( p < 0.05, false discovery rate–corrected). Discussion: Age at stroke is an important factor for poststroke recovery and modulates long-term cognitive outcome irrespective of lesion size and lesion location. Children after early childhood stroke are at particular risk for long-term alterations in cognitive functions.